Physiology of apple rootstock susceptibility to Pythium ultimum - V.K. GUPTA, I.M. SHARMA and (Indian Phytopathology, 2002)
Studies on six apple rootstocks, namely, M7, M9, M25, M103 , MM104 Â and MM115, showing different reaction to Pythium ultimum, causing collar rot of apple in Himachal Pradesh, were undertaken. In healthy (uninoculated) rootstocks, maximum amount of reducing and non-reducing sugars, higher activity of (l- amylase, invertase and protease was recorded in highly susceptible rootstocks (MM103, MM104), and minimum in resistant rootstocks (MM103, MM104). The activity of c- amylase was recorded maximum in the early stages of infection, however, the invertase and protease activity continued to increase up to 25th day of infection. The non-reducing sugars increase with a faster rate after infection only in resistant rootstocks (MM115) and their level declined in. susceptible rootstocks.